THE AFTERLIVES OF MEMORIAL MATERIALS: DATA, HOAX, BOT - Nansen , Bjorn; Hjorth, Larissa; Pitsillides, Stacey; Gould, Hannah (AoIR Selected Papers of Internet Research, 2019)
The study of death online has often intersected with questions of trust, though such questions have evolved over time to not only include relations of trust between individuals and within online communities, but also issues of trust emerging through entanglements and interactions with the afterlives of memorial materials. Papers in this panel attend to the growing significance of the afterlives of digital data, the circulation of fake deaths, the care attached to memorial bots, and the intersection of robots and funerals. Over the last twenty years the study of death online developed into a diverse field of enquiry. Early literature addressed the emergence of webpages created as online memorials and focused on their function to commemorate individuals by extending memorial artefacts from physical to digital spaces for the bereaved to gather (De Vries and Rutherford, 2004; Roberts, 2004; Roberts and Vidal, 2000; Veale, 2004). The emergence of platforms for social networking in the mid-2000s broadened the scope of research to include increasingly knotted questions around the ethics, politics and economics of death online. Scholars began investigating issues like the performance of public mourning, our obligations to and management of the digital remains of the deceased, the affordances of platforms for sharing or trolling the dead, the extraction of value from the data of the deceased, and the ontology of entities that digitally persist (e.g. Brubaker and Callison-Burch, 2016; Gibbs et al., 2015; Karppi, 2013; Marwick and Ellison, 2012; Phillips, 2011; Stokes, 2012). Scaffolding this scholarship are a number of research networks, including the Death Online Research Network and the DeathTech Research Network, who encourage international collaboration and conversation around the study of death and digital media, including supporting this AoIR panel. This panel contributes to the growing field of research on death and digital media, and in particular poses challenges to focus on the commemoration of humans to encompass broader issues around the data and materiality of digital death. Digital residues of the deceased persist within and circulate through online spaces, enrolling users into new configurations of posthumous dependence on platforms, whilst at the same time digital afterlives now intersect with new technologies to create emergent forms of agency such as chatbots and robots that extend beyond the human, demanding to be considered within the sphere of digital memorialisation. Questions of trust emerge in this panel through various kinds of relationality formed with and through digital remains. These extend from relations of trust in the digital legacies now archived within platform architectures and how we might curate conversations differently around our personal data; to the breaking of trust in the internet when creating or sharing a hoax death; to the trust involved in making and caring for a posthumous bot; to the trust granted to robots to perform funerary rites. It is anticipated that this panel will not only appeal to scholars interested in the area of death and digital media, but also engage with broader scholarly communities in which questions of death now arise in larger debates around data, materiality, and governance on and of the internet. References Brubaker, J. R. and Callison-Burch, V. (2016) Legacy Contact: Designing and Implementing Post-mortem Stewardship at Facebook. Paper presented at CHI Workshop on Human Factors in Computer Systems, San Jose California. de Vries, B. and Rutherford, J. (2004) Memorializing Loved Ones on the World Wide Web. Omega: Journal of Death and Dying, 49(1), 5-26. Gibbs, M., Meese, J., Arnold, M., Nansen, B., and Carter, M. (2015) #Funeral and Instagram: Death, Social Media and Platform Vernacular. Information Communication and Society, 18(3): 255-268. Karppi, T. (2013) Death proof: on the biopolitics and noopolitics of memorializing dead Facebook users. Culture Machine, 14, 1-20. Marwick, A. and Ellison, N. (2012) “There Isn’t Wifi in Heaven!” Negotiating Visibility on Facebook Memorial Pages. Journal of Broadcasting and Electronic Media 56(3), 378–400. Phillips, W. (2011) LOLing at Tragedy: Facebook Trolls, Memorial Pages and Resistance to Grief Online. First Monday 16(12). Retrieved from http://firstmonday.org Roberts, P. (2004) The Living and the Dead: Community in the Virtual Cemetery. Omega: Journal of Death and Dying, 49(1), 57-76. Stokes, P. (2012) Ghosts in the Machine: Do the Dead Live on in Facebook? Philosophy and Technology, 25(3), 363-379. Veale, K. (2004) Online Memorialisation: The Web as a Collective Memorial Landscape For Remembering The Dead. The Fibreculture Journal, 3. Retrieved from http://three.fibreculturejournal.org